Phytochemical screening and bioactivity studies of murraya koenigii (leaves) / Nur Aieza Fadzlin Mat Zuki - Mat Zuki, Nur Aieza Fadzlin (2017)
Ground of leave of Murraya koenigii were extracted by using cool extraction method at room temperature. Extraction were done successfully by using three different solvent which were hexane, chloroform and ethanol. Each of the extraction was evaporated by using rotary evaporator to produce crude extract. Phytochemical screening of M. koenigii also has been studied and phytochemical compound such as alkaloid, flavonoid, tannin, glycosides, steroids, sterols, triterpenoid, saponins were detected by using different test in ethanolic extract. Suitable combination of solvent system was chosen to determine the TLC profile using thin layer chromatography method. The ratio of 9:1, 7:3, 5:5, 3:7, 1:9 were used to test out the suitability of TLC profile of each different crude. Antibacterial activities were evaluate for crude extract against gram positive bacteria were Bacillus subtilis and Staphylococcus aureus and gram negative bacteria were Escherichia coli and Salmonella species. Ethanol extract showed the highest inhibition with 10 mm.against Salmonella sp meanwhile the hexane crude and chloroform crude was showed weak antibacterial activities The antioxidant properties of different extracts (hexane, chloroform and ethanol) of M. koenigii was evaluated using 2,2 diphenyl-1-picrylhyorazyl (DPPH). The percentage inhibition of different crude was obtained by using Ultraviolet-Visible (UV-VIS) spectrophotometer. The result showed that the ethanol crude extract displayed highest percentage inhibition of antioxidant compared to the hexane extract and chloroform extract.